2005
DOI: 10.4049/jimmunol.174.12.8154
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Containing Molecular Patterns Are Strong Inducers of Cyclooxygenase-2 Expression and Prostaglandin E2 Production in Human Macrophages

Abstract: The induction of cyclooxygenase-2 (COX-2) and the production of PGE2 in response to pathogen-associated molecular patterns decorated with mannose moieties were studied in human monocytes and monocyte-derived macrophages (MDM). Saccharomyces cerevisiae mannan was a robust agonist, suggesting the involvement of the mannose receptor (MR). MR expression increased along the macrophage differentiation route, as judged from both its surface display assessed by flow cytometry and the ability of MDM to ingest mannosyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 63 publications
0
36
0
Order By: Relevance
“…The MR recognizes glycosylated molecules with terminal mannose, fucose, and N-acetylglucosamine moieties (50). Its role in pathogen-triggered signaling is beginning to be appreciated (51). Nigou et al (23) have reported that Saccharomyces cerevisiae mannan could inhibit LPS-induced IL-12 release from dendritic cells.…”
Section: Specific Down-regulation Of Irak-m Abolishes the Inhibitory mentioning
confidence: 99%
“…The MR recognizes glycosylated molecules with terminal mannose, fucose, and N-acetylglucosamine moieties (50). Its role in pathogen-triggered signaling is beginning to be appreciated (51). Nigou et al (23) have reported that Saccharomyces cerevisiae mannan could inhibit LPS-induced IL-12 release from dendritic cells.…”
Section: Specific Down-regulation Of Irak-m Abolishes the Inhibitory mentioning
confidence: 99%
“…In previous studies, we have observed a robust release of AA in human monocytes (10) and polymorphonuclear leukocytes (PMN) (11) by two pathogen-associated molecular signatures, namely, peptidoglycan (PGN) and mannose-based polymers, thus defining pathogen-associated molecular patterns as chief stimuli for AA metabolism. In the present study, we addressed the effect of a set of stimuli acting through receptors involved in recognition of microbial components by DC.…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…It belongs to a family of fungal immunogenic MPs and stimulates a high production of specific antibodies (Viudes et al 2001). The main mechanism by which the MP produces the modulation of the immune response is related to mannose receptors present on dendritic cells (Mansour et al 2006;Fernández et al 2005). However, the protein portion of mannoproteins has an intrinsic capacity to stimulate a potent immune response (Pietrella et al 2008;La Valle et al 2000).…”
Section: Resultsmentioning
confidence: 99%